Multinuclear 1H/13C/15N chemical shift assignment of therapeutic octreotide acetate performed at natural abundance - Menke, Alexander J (Magnetic resonance in chemistry : MRC, 2024)
© 2024 John Wiley & Sons Ltd. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.